Partnership on Financing to Solve Limited Environmental Budget and Political Will as the Main Factor for Succes: Case in the Yogyakarta City - Indra Bastian (The Indonesian Journal of Accounting Research, 2013)
Since a regional autonomy declared in Indonesia by the Law No. 22/1999 and Law No. 25/1999, many local governments became more independent in financing of local development. Uncontrolled investment and economy activities to increase PAD can threat natural resources and result environment pollution. Eventually, the main problem of natural resources and environment conservation are a budget limitation. A limited budget has been a negative effect in an optimizing an environmental conservation effort. It is important to keep the local budget sufficiency in order to solve the environmental problems integrally and sustainable. Beside that, an identification of other factors that influence the environmental financing efforts is important to be considered.Yogyakarta City has 32,5 km2 width. It’s just 1% of total square of DIY Province. By the fact, its population density rate is the highest one in DIY as 12.246 per km2. These conditions tend to result environmental problems. But obviously, a budget allocation of Yogyakarta City for environment sector still low. It’s only 3,7% of total local budget. It should be provided for cleaning maintenance, resolve air and water pollution, and develop physical and non physical support for environmental development programs. Most of the environmental budget is allocated for general administration disbursement as 56%. However, the disbursement for operational and maintenance activities isn’t significant with the environment problems faced by the Yogyakarta City. For example, there is a solid waste disposal as 1.571 m3/days, but it is only 1.335 m3/days, which can be picked up to the final disposal unit in Piyungan. Besides, air pollution is one of the most important environment sector need to be considered. It’s only 20% of total population in Yogyakarta using mass transportation. It can be imagined that most of people prefer using private vehicle and of course it’s significant to contribute air pollution as the result of fuel emission. It can be shown by air quality inYogyakarta City nowadays is 0,9 ug/l, upper than allowed standard value 0,3 ug/l.The research will answer on how the Local Government (LG) of Yogyakarta City solves a limited budget problem to run some strategic environmental programs.